Late‐Stage Peptide Macrocyclization by Palladium‐Catalyzed Site‐Selective C−H Olefination of Tryptophan. (8th July 2020) - Bai, Zengbing; Cai, Chuangxu; Sheng, Wangjian; Ren, Yuxiang; Wang, Huan
Abstract: Transition‐metal‐catalyzed C−H activation has shown potential in the functionalization of peptides with expanded structural diversity. Herein, the development of late‐stage peptide macrocyclization methods by palladium‐catalyzed site‐selective C(sp 2 )−H olefination of tryptophan residues at the C2 and C4 positions is reported. This strategy utilizes the peptide backbone as endogenous directing groups and provides access to peptide macrocycles with unique Trp–alkene crosslinks. Abstract : A site‐selective late‐stage peptide modification and macrocyclization strategy by means of palladium‐catalyzed C(sp 2 )−H olefination of tryptophan residues at the C2 and C4 positions has been developed. TIPS=triisopropylsilyl; Tf=trifluorosulfonamide.